Validierung von Testinstrumenten durch Testmotivationsindikatoren. - Watson, Christina; Meier, Jana; Seifert, Andreas; Küth, Simon; Scholl, Daniel (DGPs-Tagung „View on of Science“, Hildesheim)

Inwiefern ist die Professionalisierung in Praxisphasen schulformspezifisch? Ergebnisse der Messung pädagogischer Kompetenzen Studierender in Deutschland. - Caruso, Carina; Seifert, Andreas (Österreichisches Religionspädagogisches Forum)

Participative human-factor evaluation in the context of digital work (re-)design - Schumacher, Jan-Philip; Depenbusch, Sarah; Straatmann, Tammo; Bender, Elena; Schaper, Niclas; Hamborg, Kai-Christoph (Work)
BACKGROUND: Challenged by digital transformation, organizations increasingly integrate information and communication technologies into work designs. Often focal points of such digital reengineering initiatives are technical and economic aspects. Yet, as integration of new technologies affects how employee work and interact, there is a need to evaluate human-centered criteria (human-factor evaluation), optimally by involving employees as situational experts. OBJECTIVE: The present study develops an integrative and persona-based evaluation approach of human-centered criteria for application in participative digital (re-)design of work to support the joint optimization of the technical and social system. METHODS: Drawing on methods from usability evaluation, a persona-based approach is developed to facilitate comprehension and application of human-centered evaluation by employees. To that end, human-centered criteria from existing evaluation models are systemized with specific reference to digital transformation of work processes. The developed approach is tested in pilot runs of three German small and medium-sized enterprises (SMEs). RESULTS: The initial overview shows a divergence of specific human-centered criteria at the detailed level. Simultaneously, a high convergence is found for overarching dimensions and categories. The Integrative Socio-Digital Evaluation Model (ISDEM) is developed to balance complexity and abstraction of criteria. The derived persona-based approach (persISDEM) shows a good applicability in the pilot runs. CONCLUSIONS: The present study provides an amendment to existing work design approaches with an emphasis on employee participation, enabling organizations to foster employees’ comprehension and motivation to engage in evaluations of digital (re-)design of work and to create motivating and healthy jobs for successful digital transformation.
Keywords: Public Health; Environmental and Occupational Health; Rehabilitation

Qualitätssicherung im bildungswissenschaftlichen Studium – methodologische Überlegungen. - Seifert, Andreas; Watson, Christina (DGPs-Tagung „View on of Science“)

Förderung von motivierenden Gesprächsstrategien im Elterngespräch. Workshop für Lehrkräfte und Studierende - Hilkenmeier, Johanna; Greiner, Christian; Bonanati, Sabrina; Buhl, Heike M. (Journal für LehrerInnenbildung)

(Be)Werten im organisationsabhängigen Interaktionssystem: das Beispiel Peer Review in Akkreditierungsverfahren von Hochschulen und Studiengängen - Schneijderberg, Christian; Götze, Nicolai; Steinhardt, Isabel; Schindler, Janosch (Zeitschrift für Evaluation)
In diesem Beitrag wird die ‚What Works‘-Debatte in der Sozialen Arbeit um die zentrale Frage nach Wirkfaktoren erweitert. Der empirische Nachweis von Wirkfaktoren in sozialarbeiterischen Interventionen ist bis heute ein Desiderat. Vor dem Hintergrund der Realist Evaluation werden in diesem Beitrag relevante Wirkfaktoren (Kontexte und Mechanismen) herausgearbeitet. Datengrundlage stellt eine Onlinebefragung von 200 fallführenden Fachpersonen in vier sozialarbeiterischen Handlungsfeldern in der deutschsprachigen Schweiz dar (Arbeitsintegration, Bewährungshilfe, Schuldnerberatung, Sozialhilfe). Die Ergebnisse verweisen auf signifi kante Wirkfaktoren von erfolgreichen Interventionen, u.a. Arbeitsstile der Fachpersonen und Verhaltensmerkmale der Klient(inn)en und können in einem allgemeinen Wirkungsmodell mit handlungsfeldübergreifenden Outcomes verdichtet werden. Diese Erkenntnisse leisten einen Beitrag zur Professionalisierung der Sozialen Arbeit sowie zur Konstruktion von Wirkungsmodellen und sollen zukünftige weitere Forschungsvorhaben in diese Richtung anregen.
Keywords: Soziologie des Wertens und Bewertens; Peer Review; Akkreditierung; Hochschule

Effects of verbal negation on TVA’s capacity and weight parameters - Banh, Ngoc Chi; Scharlau, Ingrid (TeaP 2022 - Abstracts of the 64th Conference of Experimental Psychologists)

Folgen wiederholter Negation auf die Aufmerksamkeit - Banh, Ngoc Chi; Scharlau, Ingrid; Rohlfing, Katharina J. (52. Kongress der Deutschen Gesellschaft für Psychologie)

Gesundes Misstrauen gegenüber Erklärungen - Peters, Tobias Martin; Scharlau, Ingrid (52. Kongress der Deutschen Gesellschaft für Psychologie)

Die Förderung von Reflexionskompetenz und Reflexion durch die angeleitete Bearbeitung eines weiterentwicklungsorientierten Online-Self-Assessments - Buhl, Heike M.; Sagolla, Nils; Bohndick, Carla (Lehrerbildung auf dem Prüfstand)